Evaluation of Green Elements and Thermal Comfort Condition of Assyafaah Mosque, Singapore - Noor Muhammad, Abdul Rahman; Muhammad Syukri Imran, Abullah; Chin, Haw Lim (UNIMAS Publisher, 2021)
A mosque is a place for worship and religious activities that are traditionally built with a typical design and shape with a dome and minaret as its traditional symbols. The most basic design of a mosque is a simple single-storey rectangular-shaped building with a prayer hall inside it. Design in the past was influenced by social and cultural aspects. However, regional and climatic differences have led to thermal discomfort and unnecessary energy use if the mosque is not properly designed. Therefore, there is a need to consider comprehensive planning and review for passive design to avoid thermal discomfort and excessive use of energy. Assyafaah Mosque in Singapore is one example that considers sustainable elements in its design. While Singapore is located very near to the hot equatorial line, many passive and green features have been integrated into the design and construction of the mosque, and this made it possible to achieve an acceptable thermal condition according to the adaptive and PMV thermal comfort model. The design maximizes the potential of naturally ventilated design with other passive strategies which allow for both thermal comfort and energy saving. This paper aims to study the impact of natural ventilation and other passive design decisions on the thermal comfort of the Assyafaah mosque in a hot and humid climate.